Influence of Innovation on the Performance of Small and Medium-Scale Enterprises in Kogi State - Ernest, Onogwu Eneojo; Sule, Ja'afaru Garba (Journal of Asian Business Strategy, 2020)
The main aim of the study was to investigate the influence of innovation on the performance of Small and Medium-Scale Enterprises in Kogi State, Nigeria. The study examined the significant effects of the dimensions of innovation on the sales growth of SMEs in Kogi State. The study used survey research design. The sample size of 384 was drawn. All data collected were analyzed using descriptive statistics and Multiple Regression Model. Finding shows that market and process innovations have weak linear effects on the sales growth of SMEs in Kogi State. Only product innovation has strong effect on the sales growth of SMEs in Kogi State. The study concluded that innovation is a necessary obligation for SMEs existence today. The study recommended that SME owners should undertake or invest more in market innovation rather than process innovation and product innovation to achieve sales growth in Kogi State.